Evaluation of complete blood cell count parameters and lymphocyte-related ratios in patients with Opioid Use Disorder - Baykara, Sema; Şirin Berk, Şule; Kaya, Şüheda; Ocak, Davut (Taylor and Francis Ltd., 2022)
Complete blood count (CBC) parameters and lymphocyte-related ratios are found to be associated with inflammation and increased cytokine production. In Opioid Use Disorder (OUD), CBC parameters can be examined as the inflammatory (oxidative stress) biomarkers which could be used as an objective marker to support the OUD diagnosis and could be used as a disease severity marker. CBC parameters of 142 patients with OUD were examined. Lymphocytes, monocytes, basophiles, eosinophils and platelet counts (PLT), red blood cell levels (HGB), mean erythrocyte volume (MCV) and lymphocyte-related ratios were calculated. The control group consisted of 140 healthy individuals. WBC, neutrophil, lymphocyte, monocyte, platelet count, neutrophil, basophil percentage, neutrophil/ lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR) values were significantly higher in OUD group. Lymphocyte, basophil percentage, basophile/lymphocyte ratio (BLR), red blood cell (RBC), hemoglobin were significantly higher in control group. Mean platelet volume (MPV), eosinophil/lymphocyte ratio (ELR), platelet/ lymphocyte ratio (PLR) values were not significant yet higher in the OUD group. CBC and related parameters (WBC, neutrophil, lymphocyte, monocyte, platelet count, neutrophil, basophil percentage, NLR, MLR) were found to be significantly higher in the OUD group. Evaluation of CBC parameters could be useful in treatment and follow-up of patients with OUD. © 2021 Taylor & Francis.
Keywords: addiction; blood cell count; inflammation; lymphocytes; Opioid-related disorders; platelets